Key access and utilization descriptors for pigeonpea genetic resources - Bioversity International; International Crops Research Institute for the Semi-Arid Tropics; Indian Council of Agricultural Research (2010)
This minimum list consists of an initial set of characterization and evaluation descriptors for pigeonpea utilization.